Temporary fixing composition, temporary fixing adhesive, and method for producing thin wafer
A temporary fixation composition with optimized components for low outgassing and peelability addresses the challenges of peeling thin wafers with low laser power, ensuring efficient and damage-free processing.
Patent Information
- Application Number
- JP2024509810
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-01-31
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-01-31
AI Technical Summary
Existing temporary fixing agents for thin wafers face challenges in peeling off without causing damage due to high laser power, which leads to heat generation and substrate quality issues, and require improved peelability and low outgassing properties.
A temporary fixation composition comprising specific components (A) polymerizable (meth)acrylates, (B) photoradical polymerization initiator, and (C) ultraviolet absorber with polymerizable functional groups, optimized for low outgassing and improved peelability, using a formulation that enhances the outgassing amount to facilitate easy peeling.
The composition achieves excellent peelability with low power output, reducing heat generation and substrate damage, while maintaining adhesion and durability during processing steps.
Smart Images

Figure 0007629143000001 
Figure 0007629143000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a temporary fixing composition, a temporary fixing adhesive, and a method for producing a thin wafer. [Background technology]
[0002] In the manufacture of electronic devices, inorganic materials such as silicon are often used as substrates, and wafer-type substrates with a thickness of about several hundred microns are often used, which are obtained by forming an insulating film on the surface, forming circuits, and thinning by grinding. However, since many substrates are made of brittle and easily cracked materials, measures to prevent damage are necessary, especially when thinning by grinding. A conventional method for this measure is to apply a temporary protective tape to the surface opposite to the surface to be ground (also called the back surface), which can be peeled off after the processing process is completed. This tape uses an organic resin film as the base material, and while it is flexible, it is insufficient in strength and heat resistance, making it unsuitable for use in high-temperature processes.
[0003] In response to this, a system has been proposed in which an electronic device substrate is bonded to a support member such as silicon or glass via an adhesive, thereby providing sufficient durability to withstand the conditions of the back grinding and back electrode formation processes. In this case, the adhesive layer used to bond the substrate to the support member is important. This must be able to bond the substrate to the support member without any gaps, and must be durable enough to withstand subsequent processes. Finally, it must be possible to easily peel off the thinned wafer from the support member, i.e., to temporarily fix it.
[0004] The processing of such wafers mainly involves a spin coating step, a vacuum bonding and light curing step, a thinning step by grinding and polishing, a high-temperature treatment step, a laser peeling step, and a temporary fixing agent removal step.
[0005] In the spin coating process, in order to form a uniform film of the temporary fixative on the wafer, it is required that the temporary fixative has an appropriate viscosity and is a Newtonian fluid (or has a shear viscosity that is independent of the shear rate).
[0006] In the vacuum bonding / UV curing process, the temporary fixative must be able to cure in a short time by irradiating it with ultraviolet (UV) light or other light on a supporting member such as glass, and must generate little outgassing (low outgassing properties).
[0007] In the thinning process by grinding and polishing, in order to avoid damage caused by the load of the grinding machine being applied locally to the substrate, the temporary fixative must have an appropriate hardness to distribute the load in the in-plane direction while preventing localized sinking of the substrate and maintaining flatness. In addition, adhesive strength with the supporting member, an appropriate elastic modulus to protect the edges, and chemical resistance are also required.
[0008] In the high-temperature treatment process, the temporary fixing agent is required to have heat resistance capable of withstanding high-temperature treatment in a vacuum for a long period of time (for example, at 300° C. or higher for one hour or more).
[0009] In the laser peeling process, the temporary fixative is required to be able to be peeled off quickly by a laser such as a UV laser.
[0010] In the removal step, in addition to easy removability so that the substrate can be easily peeled off from the support member, the adhesive is required to have cohesive properties so that no adhesive residue remains on the substrate after peeling, and easy cleanability.
[0011] In view of this background, for example, Patent Document 1 discloses a temporary fixing composition containing (A-1) a monofunctional (meth)acrylate whose side chain is an alkyl group having 18 or more carbon atoms and whose homopolymer has a Tg of -100°C to 60°C, (A-2) a polyfunctional (meth)acrylate, (B) a polyisobutene homopolymer and / or a polyisobutene copolymer, and (C) a photoradical polymerization initiator, and claims that the composition has excellent heat resistance, low outgassing properties, and peelability. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] International Publication No. 2021 / 235406 Summary of the Invention [Problem to be solved by the invention]
[0013] To peel off the hardened temporary fixing agent (i.e., adhesive layer) on the wafer, a laser is swept through a transparent support member such as glass to decompose the adhesive layer at the irradiated location, forming a hole (a recess that is covered with the support member). The gas vaporized in the hole expands at high temperature, pushing up the support member, making it easier to peel off.
[0014] However, when a laser is irradiated, the radiant energy is absorbed, and the irradiated area generates heat and the temperature rises. Therefore, the higher the output of the laser irradiation, the easier it is to decompose the hardened temporary fixing agent, but the temperature of the substrate adjacent to the temporary fixing agent also rises, which is not preferable from the viewpoint of ensuring the quality of the substrate.
[0015] The present invention has been completed in view of the above problems, and an object of the present invention is to provide, in one embodiment, a temporary fixing composition that has excellent peelability even when irradiated with a low-power laser. In another embodiment, the present invention is to provide a temporary fixing adhesive that includes such a temporary fixing composition, and a method for manufacturing a thin wafer using the temporary fixing adhesive. [Means for solving the problem]
[0016] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a concept different from that of the conventional technology. Specifically, as described above, a temporary fixing composition is required to have low outgassing properties, but from the viewpoint of improving the peelability, it is more desirable to increase the amount of outgassing. This is because the force required for peeling is reduced when the outgassing is present between the support member and the thin wafer. The present invention has been completed based on the above findings, and is exemplified below.
[0017] [1] A temporary fixing composition comprising the following (A) to (C): (A) A polymerizable component containing a (meth)acrylate (B) Photoradical polymerization initiator (C) UV absorber having a polymerizable functional group A temporary fixing composition, characterized in that the amount of outgassing measured by the following procedure is 0.75% or more. A temporary fixing composition of 50 mm x 50 mm x 0.07 mm was molded onto a round glass plate whose mass (A0) had been measured in advance, and the mixture was irradiated with a black light of 365 nm wavelength at an illumination intensity of 100 mW / cm under a nitrogen atmosphere. 2 , irradiation time 50 seconds, cumulative light intensity 5000mJ / cm 2 The test piece is cured under the above conditions to obtain a test piece. After measuring the mass (A1) of the test piece, it is irradiated with a 355 nm UV laser (output: 6 W, spot diameter: 200 μm, irradiation pitch: 200 μm, scan speed: 8 m / sec, frequency: 40 Hz) and the mass (A2) of the test piece after irradiation is measured. The amount of outgassing is calculated from the mass obtained by these procedures and the following formula. Outgassing amount (%) = ((A1-A2) / (A1-A0)) x 100 [2] The temporary fixing composition according to [1], wherein the component (A) is a polymerizable component that does not have a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, or a phenol skeleton, and has a (meth)acryloyl group. [3] The temporary fixing composition according to [1] or [2], wherein the component (B) is one or more selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime). [4] The temporary fixing composition according to any one of [1] to [3], wherein the component (C) has one or more skeletons selected from the group consisting of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton, and has a polymerizable functional group. [5] The temporary fixing composition according to any one of [1] to [4], containing 0.01 to 5 parts by mass of the (B) component and 0.01 to 12 parts by mass of the (C) component relative to a total of 100 parts by mass of the (A) component. [6] A temporary fixing adhesive comprising the temporary fixing composition according to any one of [1] to [5]. [7] A method for producing a thin wafer using the temporary fixing adhesive described in [6]. Effect of the Invention
[0018] According to one embodiment of the present invention, it is possible to provide a temporary fixing composition having excellent peelability even when irradiated with a low-power laser. In another embodiment, the present invention can provide a temporary fixing adhesive containing such a temporary fixing composition, and a method for producing a thin wafer using the temporary fixing adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Next, the embodiments of the present invention will be described in detail. It should be understood that the present invention is not limited to the following embodiments, and that appropriate design changes, improvements, etc. may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0020] In this specification, unless otherwise specified, the numerical range includes the upper and lower limits. In this specification, (meth)acrylate refers to a compound having one or more (meth)acryloyl groups in one molecule. Monofunctional (meth)acrylate refers to a compound having one (meth)acryloyl group in one molecule. Multifunctional (meth)acrylate refers to a compound having two or more (meth)acryloyl groups in one molecule. n-functional (meth)acrylate refers to a compound having n (meth)acryloyl groups in one molecule. The polymerizable functional group in the multifunctional (meth)acrylate may have only an acryloyl group, may have only a methacryloyl group, or may have both an acryloyl group and a methacryloyl group.
[0021] (1. Component (A)) The polymerizable component (A) contained in the temporary fixing composition of this embodiment plays a role in forming a (meth)acrylic polymer skeleton. The temporary fixing composition of this embodiment may also contain a non-polymerizable component, but the amount of the non-polymerizable component is preferably less than 15 parts by mass per 100 parts by mass of the total of the non-polymerizable component and the (A) component. In this specification, the term "non-polymerizable component" is defined as anything other than the (B) component, i.e., anything not used in the technical field as a photoradical polymerization initiator.
[0022] The polymerizable component (A) contained in the temporary fixing composition of this embodiment has a (meth)acryloyl group and plays a role in forming a (meth)acrylic polymer skeleton. The polymerizable component is preferably a polymerizable organic compound component. The component (A) may preferably contain a compound having two or more (meth)acryloyl groups. The component (A) may be a monofunctional (meth)acrylate, a bifunctional (meth)acrylate, a trifunctional or higher polyfunctional (meth)acrylate, or a mixture thereof. Also preferably, the (A) component may include a combination of a polyfunctional (meth)acrylate and a monofunctional (meth)acrylate (more preferably a combination of a bifunctional (meth)acrylate and a monofunctional (meth)acrylate), a combination of a polyfunctional (meth)acrylate and a polymerizable polymer (more preferably a combination of a bifunctional (meth)acrylate and a polymerizable polymer), or a combination of a polyfunctional (meth)acrylate, a monofunctional (meth)acrylate and a polymerizable polymer (more preferably a combination of a bifunctional (meth)acrylate, a monofunctional (meth)acrylate and a polymerizable polymer). The (A) component does not have any of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton (i.e., it does not include the (C) component described below). The (A) component preferably does not have a nitrogen atom in the molecule.
[0023] The polyfunctional (meth)acrylate that the (A) component may contain may be an aromatic bifunctional (meth)acrylate, an alicyclic bifunctional (meth)acrylate, or a mixture thereof, from the viewpoint of providing a rigid structure. The (A) component may contain an acyclic polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate may be a monomer or a polymer, or a mixture thereof. That is, the above-mentioned polymerizable polymer may be a polymer of a polyfunctional (meth)acrylate. The molecular weight of the polyfunctional (meth)acrylate monomer is preferably 900 or less, more preferably 700 or less, even more preferably 500 or less, and even more preferably 400 or less.
[0024] Examples of aromatic bifunctional (meth)acrylates include 9,9-bis[4-(2-hydroxy C1-C 20 Alkoxy)phenyl]fluoren-di(meth)acrylate, C1-C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20 Examples of the di(meth)acrylate include 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, and structural isomers thereof. Preferably, the di(meth)acrylate may include a di(meth)acrylate having a condensed ring skeleton, such as a skeleton of fluorene, indene, indecene, anthracene, azulene, or triphenylene.
[0025] Examples of alicyclic bifunctional (meth)acrylates include C1-C 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, 1,3-di(meth)acryloyloxyadamantane, tricyclo C 10 ~C 20 Alkanedimethanol di(meth)acrylate, dicyclo C5-C 20 di(meth)acrylate, or a structural isomer thereof.
[0026] Examples of the acyclic bifunctional (meth)acrylate include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and caprolactone modified hydroxypivalic acid neopentyl glycol di(meth)acrylate.
[0027] The component (A) may also contain a polyfunctional (meth)acrylate having three or more functional groups. Examples of the trifunctional (meth)acrylate include isocyanuric acid ethylene oxide modified tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tris[(meth)acryloyloxyethyl]isocyanurate.
[0028] Examples of tetrafunctional or higher (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0029] Furthermore, the monofunctional (meth)acrylate that may be contained in the component (A) is preferably a monofunctional (meth)acrylate having a molecular weight of 550 or less, and more preferably a monofunctional alkyl (meth)acrylate having an alkyl group.
[0030] The alkyl group is preferably one or more selected from linear alkyl groups, branched alkyl groups, and alicyclic alkyl groups, and more preferably one or more selected from linear alkyl groups and branched alkyl groups. From the viewpoint of improving compatibility with other components, it is preferable that the (A) component has a long chain and branched or cyclic alkyl group, for example, a branched alkyl group having 18 to 40 carbon atoms, more preferably 18 to 32 carbon atoms, such as an isostearyl group, an isotetracosanyl group (e.g., 2-decyl-1-tetradecanyl group), an isotriacontanyl group (e.g., 2-tetradecyl-1-octadecanyl group), or a cycloalkyl group. By using such a component having a long chain, high molecular weight, and strong aliphatic hydrocarbon properties (more preferably by increasing the aliphatic hydrocarbon properties of the entire system), it is possible to improve the low volatility, chemical resistance, and heat resistance required for the temporary fixing composition.
[0031] As the (A) component, one or more selected from the group consisting of stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, 2-dodecyl-1-hexadecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate are preferred. As the (A) component, the (meth)acrylate of the following formula 1 is preferred.
[0032] [ka] In the formula, R 1 R is a hydrogen atom or a methyl group, and a hydrogen atom is more preferable. 2 is an alkyl group having a carbon number of preferably 18 to 32. One or more of these (meth)acrylates can be used.
[0033] R 2As the monofunctional alkyl (meth)acrylate in which is an alkyl group having 18 to 32 carbon atoms, preferred are (meth)acrylates having a linear or branched alkyl group, such as stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicodecyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate.
[0034] In a preferred embodiment, the amount of the non-polymerizable component contained in the temporary fixing composition of the present embodiment may be 0 mass% or more and less than 10 mass%, or 0 mass% or more and less than 5 mass%. More preferably, the temporary fixing composition of the present embodiment may not contain any non-polymerizable component except for the component (B).
[0035] (2.(B) component) The photoradical polymerization initiator, which is the component (B) contained in the temporary fixing composition of the present embodiment, is a substance that can initiate polymerization of the component (A) upon irradiation with light. The photoradical polymerization initiator is, for example, a compound whose molecule is cleaved and split into two or more radicals upon irradiation with ultraviolet light or visible light (e.g., wavelength 350 to 700 nm, preferably 365 to 500 nm, more preferably 385 to 450 nm). Examples of photoradical polymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime). The component (B) may contain one or more of these, or a combination of two or more of them.
[0036] In a preferred embodiment of the present invention, the component (B) contained in the temporary fixing composition may contain an acylphosphine oxide-based compound. Examples of preferred acylphosphine oxide-based compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. As the photoradical polymerization initiator, it is preferable that it is highly sensitive, has excellent deep curing properties due to its photofading properties, and has an absorption wavelength range for generating radicals that extends to a relatively long wavelength range. In the above-mentioned preferred compounds, the absorption wavelength range is in the range up to a wavelength of about 440 nm, which is significantly different from the absorption wavelength range of the UV absorber used in the UV laser peeling process described later. In other words, the degree of UV curing inhibition by the UV absorber is small, and radical polymerization can be initiated with light of a longer wavelength. Therefore, even in the coexistence of a UV absorber, the effect of initiating radical polymerization and curing efficiently at a relatively high speed can be obtained.
[0037] In a preferred embodiment, the photoradical polymerization initiator can be selected based on absorbance. Specifically, the photoradical polymerization initiator can be selected from one or more compounds that satisfy one or more of the following conditions when dissolved at a concentration of 0.1 mass % in a solvent (e.g., acetonitrile, toluene, etc.) that does not have a maximum absorption in the wavelength region of 300 to 500 nm: absorbance of 0.5 or more at a wavelength of 365 nm, absorbance of 0.5 or more at a wavelength of 385 nm, and absorbance of 0.5 or more at a wavelength of 405 nm. Examples of compounds that satisfy such conditions include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime), which has an absorbance of 0.5 or more at a wavelength of 365 nm when dissolved in acetonitrile as a solvent at a concentration of 0.1% by mass; 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, which has an absorbance of 0.5 or more at wavelengths of 365 nm and 385 nm; and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide, which have an absorbance of 0.5 or more at wavelengths of 365 nm, 385 nm, and 405 nm.
[0038] In addition, from the viewpoint of achieving both the curing property by the photoradical polymerization initiator and the UV laser peeling, bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, which has an absorption wavelength range of 400 to 500 nm, can also be used as the photoradical polymerization initiator.
[0039] As the (B) photoradical polymerization initiator, one or more selected from acylphosphine oxide compounds, titanocene compounds, and α-aminoalkylphenone compounds are preferred in terms of reaction speed, heat resistance after curing, low outgassing, and absorption characteristics in a region different from the wavelength of the UV laser used in the UV laser peeling described later and the absorption wavelength region of the UV absorber used in the UV laser peeling. In addition to the above, oxime ester compounds can also be selected as photoradical polymerization initiators for resin compositions for temporary fixing applications for preventing damage from bonding of the substrate to be processed to the support member to the heating step, which is not a layer for responding to the UV laser peeling step, among the temporary fixing compositions having the structure described later.
[0040] Examples of the acylphosphine oxide compound include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc. Among these, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is particularly preferred.
[0041] The titanocene compound may be bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium.
[0042] Examples of the α-aminoalkylphenone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, and the like.
[0043] Examples of oxime ester compounds include 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime), etc. Among these, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime) is preferred.
[0044] In a preferred embodiment of the present invention, the component (B) in the temporary fixing composition is one or more selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime).
[0045] The amount of the photoradical polymerization initiator (B) used is preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, even more preferably 0.1 to 2 parts by mass, and even more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the total of the components (A) in terms of reaction rate, heat resistance after curing, and low outgassing. When the amount of the component (B) is 0.01 part by mass or more, sufficient curability is obtained, and when it is 5 parts by mass or less, the effect of low outgassing and heat resistance being less likely to be impaired is obtained.
[0046] (3.(C) component) The ultraviolet absorber (UV absorber) having a polymerizable functional group, which is the component (C) contained in the temporary fixing composition of this embodiment, refers to a compound whose molecules are cut and decomposed / vaporized by irradiation with ultraviolet or visible light laser, and the decomposition / vaporization occurs at the interface between the supporting member and the temporary fixing agent, causing the loss of adhesive strength between the temporary fixing agent and the supporting member that was maintained until just before the UV laser peeling step. The component (C) is a compound having one or more skeletons selected from the group consisting of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton (preferably a hindered phenol skeleton). The reason for having these skeletons is to obtain the degree of overlap with the UV laser wavelength in the UV absorption wavelength region, UV absorption characteristics at the same wavelength, low outgassing properties, and heat resistance. The polymerizable functional group of the component (C) is preferably a (meth)acryloyl group.
[0047] Examples of the component (C) include one or more members selected from the group consisting of 2-[2-hydroxy-5-[2-((meth)acryloyloxy)ethyl]phenyl]-2H-benzotriazole, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl (meth)acrylate, 2-(2-(meth)acryloyloxy,5-methyl)phenyl-2H-benzotriazole, 1,1-bis-[2-(meth)acryloyloxy,3-(2H-benzotriazol-2-yl),5-tertiaryoctyl]methane, and 2,2'-dihydroxy-4,4'-di(meth)acryloyloxybenzophenone, which are particularly preferred in terms of compatibility with the resin component, UV absorption characteristics, low outgassing, and heat resistance.
[0048] The amount of component (C) is preferably 0.01 to 12 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 0.5 to 7 parts by mass, relative to 100 parts by mass of the total of components (A). When it is 0.01 part by mass or more, a sufficient UV laser peeling speed is obtained, and when it is 12 parts by mass or less, the effect of low outgassing properties and heat resistance being less likely to be impaired is obtained.
[0049] (4. Temporary Fixing Composition) The temporary fixing composition of the present invention has an outgassing amount of 0.75% or more as measured by the following procedure. A temporary fixing composition of 50 mm x 50 mm x 0.07 mm was molded onto a round glass plate whose mass (A0) had been measured in advance, and the mixture was irradiated with a black light of 365 nm wavelength at an illumination intensity of 100 mW / cm under a nitrogen atmosphere. 2 , irradiation time 50 seconds, cumulative light intensity 5000mJ / cm 2 The test piece is cured under the above conditions to obtain a test piece. After measuring the mass (A1) of the test piece, it is irradiated with a 355 nm UV laser (output: 6 W, spot diameter: 200 μm, irradiation pitch: 200 μm, scan speed: 8 m / sec, frequency: 40 Hz) and the mass (A2) of the test piece after irradiation is measured. The amount of outgassing is calculated from the mass obtained by these procedures and the following formula. Outgassing amount (%) = ((A1-A2) / (A1-A0)) x 100
[0050] If the amount of outgas is large, the amount of outgas between the support member and the thin wafer is abundant, so that the peeling force required to peel the two is small, and the peeling property is improved. From this viewpoint, the amount of outgas measured by the above procedure is preferably 1.00% or more, more preferably 1.25% or more, and even more preferably 1.50% or more.
[0051] There is no particular upper limit for the amount of outgassing measured by the above procedure, but in order to strike a balance between ease of production and improved peelability, it is typically 10.0% or less, and more typically 5.00% or less.
[0052] The composition of the temporary fixing composition is not particularly limited as long as the amount of outgassing can be made 0.75% or more. For example, the amount of outgassing can be increased by increasing the amount of a compound having a functional group capable of absorbing laser light, or by applying a compound having a large number of functional groups capable of absorbing laser light contained in one molecule.
[0053] (5. Temporary Fixing Adhesive) The temporary fixing composition of the present invention can be used as a temporary fixing adhesive, particularly as a temporary fixing adhesive for the production of electronic devices such as thin wafers, etc. The temporary fixing adhesive preferably consists solely of the temporary fixing composition of the present invention.
[0054] (6. Thin Wafer Manufacturing Method) In another embodiment, the present invention also provides a method for manufacturing a thin wafer using the temporary fixing adhesive of the present invention, the method including applying the temporary fixing adhesive to a support member, adhering a substrate to be processed to the support member on the surface of the support member to which the temporary fixing adhesive has been applied, performing a thinning process on the substrate to be processed, and peeling off the support member and the substrate to be processed by irradiating with a UV laser.
[0055] The method for bonding the thin wafer substrate and the optically transparent support member is not particularly limited, but is typically performed by applying a temporary fixing adhesive to the optically transparent support member and then bonding the substrate to the surface on which the temporary fixing adhesive has been applied.
[0056] The temporary fixing adhesive can be applied by known application methods such as spin coating, screen printing, and various coaters. The viscosity of the temporary fixing composition of the present embodiment is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more, at 23°C (atmospheric pressure), in terms of applicability and workability. The viscosity of the temporary fixing composition of the present embodiment is preferably 15000 mPa·s or less, more preferably 10000 mPa·s or less, and even more preferably 5000 mPa·s or less, at 23°C (atmospheric pressure), in terms of applicability and workability. When the viscosity is 500 mPa·s or more, the composition has excellent applicability, particularly applicability by spin coating. When the viscosity is 15000 mPa·s or less, the composition has excellent workability. The viscosity can be measured by a known viscometer.
[0057] Spin coating is a method for applying the composition to the surface of a support member by, for example, dropping a liquid composition onto the support member and rotating the support member at a predetermined rotation speed. By spin coating, a high-quality coating film can be efficiently produced.
[0058] When bonding the substrate to be processed and the supporting member, the energy amount is 1 to 20,000 mJ / cm in visible light or ultraviolet light (wavelength or central wavelength 365 to 405 nm). 2 It is preferable to irradiate so that the energy amount is 1 mJ / cm 2 Above this level, sufficient adhesion is obtained, and 20,000 mJ / cm 2 If the energy level is less than this, the productivity is excellent, decomposition products from the photoradical polymerization initiator are unlikely to be generated, and outgassing is suppressed. In terms of productivity, adhesion, low outgassing, and easy peeling, it is 1000 to 10000 mJ / cm 2 It is preferable that:
[0059] Although there is no particular restriction on the substrate to be processed and the support member, it is preferable that at least one of the substrates is a transparent substrate that transmits light. Examples of the transparent substrate include inorganic substrates such as crystal, glass, quartz, calcium fluoride, magnesium fluoride, and organic substrates such as plastic. Among these, inorganic substrates are preferable because they are versatile and can provide a large effect. Among the inorganic substrates, one or more selected from glass and quartz are preferable.
[0060] After bonding the substrate to the support member, the substrate is processed to form a thin wafer, typically by thinning through grinding and polishing, and high-temperature treatment.
[0061] After forming the thin wafer, it is possible to peel it off by irradiating the entire surface of the adhesive body from the optically transparent substrate side with a UV laser in a scanning manner. As described above, by using the temporary fixing composition of the present invention, re-adhesion between the support and the thin wafer is suppressed, so that even if there is a certain amount of time between irradiation with a UV laser and peeling, the deterioration of workability is prevented. EXAMPLES
[0062] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to these.
[0063] Unless otherwise specified, the experiments were performed at 23°C and 50% humidity. Curable resin compositions (hereinafter sometimes referred to as liquid compositions) having the compositions (units: parts by mass) shown in the table below were prepared and evaluated. The following compounds were selected as each component.
[0064] (composition) The following was used as component (A): APB-001 (multifunctional acrylate polymer, Negami Chemical Industries "APB-001", weight average molecular weight 72,000) A-BPEF-2: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate ("NK Ester A-BPEF-2" manufactured by Shin-Nakamura Chemical Co., Ltd.) HBPE-4: EO modified hydrogenated bisphenol A diacrylate ("HBPE-4" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., m+n≒4) A-DOD-N: 1,10-decanediol diacrylate ("A-DOD-N" manufactured by Shin-Nakamura Chemical Co., Ltd.) M-113: Nonylphenol EO modified acrylate ("Aronix M-113" manufactured by Toagosei Co., Ltd., n ≒ 4) ISTA: Isostearyl acrylate ("ISTA" manufactured by Osaka Organic Chemical Industry Co., Ltd.)
[0065] Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BASF "Irgacure 819") was used as component (B).
[0066] The following was used as component (C): RUVA-93: 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole (Otsuka Chemical Co., Ltd. "RUVA-93") P-66: 2,2'-dihydroxy-4,4'-diacryloyloxybenzophenone (Daiwa Chemical Industry Co., Ltd. "DAINSORB P-66")
[0067] (Liquid sample preparation) As shown in Table 1, for each of the comparative examples and examples, the materials were heated and mixed at 60° C. to form a homogeneous liquid composition.
[0068] (Measurement of outgassing amount) A 50 mm x 50 mm x 0.07 mm mold was prepared on a round glass plate with a diameter of 100 mm and a thickness of 0.7 mm using Teflon (registered trademark) tape, and the temporary fixing composition was poured into it. Under a nitrogen atmosphere, the mold was exposed to a black light with a wavelength of 365 nm and an illumination intensity of 100 mW / cm 2 , irradiation time 50 seconds, cumulative light intensity 5000mJ / cm 2 The test piece was cured under the following conditions. The surface of the test piece on which the temporary fixing composition was applied after curing was irradiated with a 355 nm UV laser (output: 6 W, spot diameter: 200 μm, irradiation pitch: 200 μm, scan speed: 8 m / sec, frequency: 40 Hz) over the entire surface. The mass of the round glass plate used was A0, the mass of the test piece before the laser irradiation was A1, and the mass of the test piece after the laser irradiation was A2, and the amount of outgassing was calculated according to the following formula. Outgassing amount (%) = ((A1-A2) / (A1-A0)) x 100
[0069] (Preparation of bonding samples) A 4-inch silicon wafer (diameter 10 cm × thickness 0.47 mm) and a 4-inch glass support member (diameter 10 cm × thickness 0.7 mm) were bonded together using the liquid composition. The thickness of the liquid composition was adjusted to 50 μm during bonding. After bonding, the wafer was irradiated with a black light having a wavelength of 365 nm at an illumination intensity of 100 mW / cm. 2 , irradiation time 50 seconds, cumulative light intensity 5000mJ / cm 2 The liquid composition was applied to the entire surface of the bonding surface.
[0070] (Evaluation of laser peelability) The 4-inch test specimen obtained was irradiated with a UV laser having a wavelength of 355 nm on a circular area having a diameter of 110 mm fixed at the center of the test specimen so as to scan the entire surface of the test specimen from the glass support member side. A razor blade was applied to the circumference of the test specimen after the laser irradiation to remove the protruding part from the circumference. This test specimen was placed on a porous chuck type suction table with the silicon wafer facing down, and three suction cups having a diameter of 30 mm were attached from above to the glass surface of the test specimen in a fixed state. A load measuring module was attached to the suction cups, and the load applied to the glass peeling was measured by pulling it up vertically upward. As a parameter for evaluating the peelability, the laser output (W) required for glass peeling to be possible up to a load of 10 N was measured and shown in Table 1. The smaller the value, the easier the peeling.
[0071] The joined surface of the glass support member that had been peeled off using the method described above was wiped clean with a cloth soaked in acetone. It was then wiped clean with a cloth soaked in isopropanol. The glass was observed at 10x magnification using a metallurgical microscope to check for the presence of laser marks, cracks, glue residue (residual temporary fixative), etc. on the glass surface. If there were no laser marks, cracks, glue residue, etc., it was rated as "Good", and if not, it was rated as "Poor". The results are shown in Table 1.
[0072] In addition, for the bonded body of the silicon wafer and the liquid composition from which the glass support member had been peeled off by the method described above, a peeling tape (Elegrip P tape manufactured by Denka) was applied to the entire surface of the liquid composition. Immediately after that, the peeling tape was peeled off at an angle of 180° to remove the liquid composition. The silicon wafer from which the liquid composition had been removed was observed at 10 times magnification using a metallurgical microscope to check whether any adhesive residue remained on the silicon wafer surface. If no adhesive residue remained, it was evaluated as "good", and if not, it was evaluated as "bad". The results are shown in Table 1.
[0073] [Table 1]
[0074] From the results in Table 1, it was found that the temporary fixing composition of the present invention has a low laser output that requires peeling and has high peelability, which enables peeling in a state where heat generation is suppressed.
[0075] On the other hand, in Comparative Examples 1 and 2, in which the amount of outgassing was small, the laser output required for peeling was high, and peelability was poor.
Claims
1. A temporary fixing composition comprising the following (A) to (C): (A) A polymerizable component containing a (meth)acrylate (B) a photoradical polymerization initiator, which is at least one selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime); (C) UV absorber having a polymerizable functional group A temporary fixing composition, characterized in that the amount of outgassing measured by the following procedure is 0.75% or more. In advance, mass (A 0 A temporary fixing composition of 50 mm × 50 mm × 0.07 mm was molded onto the round glass plate on which the thermal expansion coefficient (Tc) was measured, and the composition was irradiated with a black light of 365 nm wavelength at an illumination intensity of 100 mW / cm under a nitrogen atmosphere. 2 , irradiation time 50 seconds, cumulative light amount 5000 mJ / cm 2 The test piece is cured under the above conditions to obtain a test piece. 1 After measuring the mass (A), the test piece was irradiated with a 355 nm UV laser (output: 6 W, spot diameter: 200 μm, irradiation pitch: 200 μm, scan speed: 8 m / sec, frequency: 40 Hz). 2 The amount of outgassing is calculated from the mass obtained by these procedures and the following formula. Outgas generation amount (%) = ((A 1 -A 2 ) / (A 1 -A 0 )) x 100
2. The temporary fixing composition according to claim 1, wherein the component (A) is a polymerizable component that does not have a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, or a phenol skeleton and has a (meth)acryloyl group.
3. The temporary fixing composition according to claim 1 or 2, wherein the component (C) has one or more skeletons selected from the group consisting of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton, and has a polymerizable functional group.
4. The temporary fixing composition according to claim 1 or 2, wherein the (B) component is contained in an amount of 0.01 to 5 parts by mass and the (C) component is contained in an amount of 0.01 to 12 parts by mass, relative to a total of 100 parts by mass of the (A) component.
5. A temporary fixing adhesive comprising the temporary fixing composition according to claim 1 or 2.
6. A method for producing a thin wafer, using the temporary fixing adhesive according to claim 5.
Citation Information
Patent Citations
Tape for grinding rear of wafer and usage thereof
JP1994177094A
Semiconductor wafer processing tape
JP2002510862A
Photocurable composition
JP2006522839A
Adhesive composition and adhesion method thereof, and peeling method after adhesion
JP2014101495A
Laminate and method for producing the same, method for manufacturing electronic component, and method for improving adhesiveness between separation layer and substrate in laminate
JP2018001604A